PROFIL PROTEIN DAGING IKAN BANDENG (Chanos chanos) MENGGUNAKAN SDS-PAGE SEBELUM DAN SESUDAH PENGGARAMAN - Feri Feri; Stalis Norma Ethica; Ana Hidayati Mukaromah (Universitas Muhammadiyah Semarang, 2017)
Milkfish (Chanos chanos) is potential source of easily digested, yet easily decayed animal protein. Salting using table salt (NaCl) is a common technique used to prevent early spoilage on milkfish meat. In study, the effect of salting on of milkfish was investigated using SDS-PAGE method. The aim were: 1. To evaluate protein profile before and after salting in milkfish at varied salt concentration and salting time. 2. To recommend milkfish salting process based on denaturation level of protein reflected by changes in protein profile compared to that of control. Seven portionsof meat from one fresh milkfish was used as samples (6 portions) and control (1 portion). All samples were salted using NaCl at concentration of 10, 20, and 30% b/b in varied salting time of 30 and 60 mins. The results showed that the milkfish meat before salting process (control) had atotal 15 protein bands. The total protein band number decreased in samples salted for 30 mins at NaCl concentrations of 10, 20 and 30% b/v to become 14, 14 and 12 bands respectively. Further decrease of the band number was observed in samples salted for 60 mins at NaCl concentrations of 10, 20 and 30% b/v where the number became 12, 11 and 10, respectively. Molecular weightanalysis on these results showed that salting process of milkfish for 30 min at NaCl concentration of 10% b/v is most recommended as its profile protein showed the least change of protein bands from control’s.Keywors: Penggaraman, Ikan bandeng profil protein, SDS-PAGE